2014
DOI: 10.1016/j.msea.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Friction-stir welding of an Al–Mg–Sc–Zr alloy in as-fabricated and work-hardened conditions

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. b s t r a c tThe effect of prior work hardening on the microstructure and mechanical properties of a friction-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 38 publications
8
43
0
2
Order By: Relevance
“…In addition, the changes of wrinkle behaviour in the PWCRed-40% sample are consistent with the ideas of a homogeneously uniform distribution of the dislocations. The uniform plastic flow is suggested to occur in those subjected to a regular form and finer grain of Al [49][50][51]. Cold working leads to two remarkable changes in the microstructure of materials, namely, grain size and dislocation density, which in turn affect the performance enhancement of the materials.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…In addition, the changes of wrinkle behaviour in the PWCRed-40% sample are consistent with the ideas of a homogeneously uniform distribution of the dislocations. The uniform plastic flow is suggested to occur in those subjected to a regular form and finer grain of Al [49][50][51]. Cold working leads to two remarkable changes in the microstructure of materials, namely, grain size and dislocation density, which in turn affect the performance enhancement of the materials.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…Therefore, the conventional technologies are obviously not appropriate for this processing route. In contrast, the friction-stir welding (FSW) technique enables preservation of the fine-grained structure [10][11][12][13][14] and avoids dissolution of the unique Al 3 Sc dispersoids [7][8][9][14][15][16][17][18][19][20] in the weld zone, making FSW particularly promising for use in the joining of UFG Al-Mg-Sc alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the conventional technologies are obviously not appropriate for this processing route. In contrast, the friction-stir welding (FSW) technique enables preservation of the fine-grained structure [10][11][12][13][14] and avoids dissolution of the unique Al 3 Sc dispersoids [7][8][9][14][15][16][17][18][19][20] in the weld zone, making FSW particularly promising for use in the joining of UFG Al-Mg-Sc alloys.Recent studies have demonstrated that friction-stir processed Al-Mg-Sc alloys exhibit excellent superplastic properties [21][22][23][24][25][26][27][28]. Specifically, the maximum elongation-to-failure value may sometimes exceed 2000% [21, 24, 27].…”
mentioning
confidence: 99%
“…It has been reported that the cooling rate elevates with increasing pin eccentricity [33]; however, the application of pin eccentricity hardly affected the evolution of strengthening precipitates in the present work. Based on our previous studies [34], coarsening proceeds rapidly if there is an existing population of precipitates available for growth: the amount of initial GP zones in the matrix is high, and thus, the coarsening proceeds completely in a relatively short period, weakening the impact of the cooling rate, and therefore, the distribution and morphology of strengthening precipitates in all joints are similar. Figure 10 shows the hardness results of FSW joints produced by different pin-eccentric stir tools, and the hardness distribution profile was asymmetric due to the different mechanical properties between AA5052 and AA6061.…”
Section: The Macro and Microstructure Of Nugget Zone Produced By Pin-mentioning
confidence: 92%
“…The inhomogeneous microstructure led to the mixed fracture and reduced the plasticity of the joints. By contrast, the fracture surfaces of joints P0.4 and P0.8 were characterized by fine and round equiaxed dimples, which indicated that the application of pin eccentricity homogenized the microstructures in the NZ and the mode of failure changes into ductile fractures [34], increasing the plasticity of pineccentric FSW joints. The average hardness of the NZ elevated as the pin eccentricity increased, which elevated from 61 HV for joint P0 to 66 HV for joint P0.8 (Figure 10b).…”
Section: The Mechanical Properties Of Pin-eccentric Fsw Jointsmentioning
confidence: 92%